The Effect Of Project Based Learning (PjBL) Model On Creative Thinking Ability of Student. - Nurfitha Kusumaningtyas; Darlen Sikumbang; Neni Hasnunidah (Universitas Lampung, 2020)
This study aims to find out the effect of Project Based Learning (PjBL) models on students' creative thinking abilities. The population was all students of class X SMA 7 Bandar Lampung that treated by 204 students. The samples were students of class X.B as class of PjBL and X.C as discovery learning which were selected from the population by cluster random sampling technique. This quasi-experimental research used the Non-Equivalent Pretest-Posttest Control Group design. Data were statistically analyzed using Ancova and LSD. The results showed that PjBL model had a significant effect on the ability to think creatively with a significance number of 0,000 (p 0.05). The mean value of students' creative thinking abilities in the PjBL class ( = 87.33) higher than the average value of the discovery learning class( = 75.17).Penelitian ini bertujuan untuk mengetahui pengaruh penggunaan model Project Based Learning (PjBL) terhadap kemampuan berpikir kreatif peserta didik. Populasi penelitian adalah peserta didik kelas X SMA Negeri 7 Bandar Lampung sejumlah 204 peserta didik. Sampel penelitian adalah peserta didik kelas X.B sebagai kelas PjBL dan X.C sebagai kelas discovery learning yang dipilih dari populasi dengan teknik cluster random sampling. Penelitian kuasi eksperimen ini menggunakan desain Pretest-Posttest Control Group Non Equivalent. Data dianalisis secara statistik dengan uji Ankova dan uji BNT. Hasil penelitian menunjukkan bahwa model PjBL berpengaruh signifikan (sig= 0,000; p0,05) terhadap kemampuan berpikir kreatif. Rerata nilai kemampuan berpikir kreatif peserta didik pada PjBL ( = 87,33) lebih tinggi dari rerata pada kelas discovery learning ( =75,17). Kata kunci: kemampuan berpikir kreatif, discovery learning, project based learning